The Future Energy Production from Aluminum and Water With Carbon Catalyst From Rice Husk - Safii, Farhan Fikri (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2021)
Hydrogen is an environmentally friendly fuel that is promoted as one of the most promising alternative energies to replace fossil fuels. The production of hydrogen through the hydrolysis reaction of aluminum is a solution to overcome the problems in the current hydrogen production method. The production of hydrogen through the hydrolysis of aluminum is an environmentally friendly process because this process produces hydrogen and AlOOH or Al(OH)3 which are easily biodegradable in nature. However, this reaction has a low reaction rate so a catalyst is needed to increase the reaction rate. In this study, carbon catalyst from coconut shell waste which was carbonated at a temperature of 800 °C and activated with 1M sulfuric acid had been successfully synthesized by electrolysis method with 0.01 NaOH solution; 0.1; 1 M. The morphological structure of the carbon catalyst produced has the same shape as activated carbon from coconut shells, which is amorphous. The SEM-EDX results showed that the carbon catalyst electrolyzed with 0.01 M NaOH had the highest metal content of Na, which was 3.68 wt%. Meanwhile, 0.1 and 1 M have Na metal content of 2.17% and Na 2.54 wt%. The results of Thermal Gravimetric Analysis (TGA) show that the thermal stability of the carbon catalyst is higher than that of activated carbon. Surface area analysis by Brunauer-Emmett-Teller (BET) showed that the activated carbon and the synthesized carbon catalyst had microporous and mesoporous structures simultaneously. The electrolyzed carbon catalyst with 0.1 M NaOH has the largest surface area of 512,2 m2/g. While the electrolyzed carbon catalyst with 0.01 M has the smallest surface area of 393,189 m2/g. The effectiveness of the carbon catalyst is known from the amount of aluminum oxidized. The carbon catalyst electrolyzed with 0.01 M NaOH was found to be the most effective because it was able to oxidize 9.17% aluminum, while the carbon catalyst electrolyzed with 0.1 and 1 M NaOH was only able to oxidize 6.85 and 7.96 aluminum, respectively. %.